Історія і зміст лінійної концепції глобального розвитку - Тишкун, Юрій (Lviv Politechnic Publіshing House, 2016)
Розглянуто поняття глобального розвитку – змін людства: кількісних (його матеріальних показників) і якісних (його природи), структурних. Стверджено, що ідейні витоки концепції розвитку закорінені в есхатології, вігівському баченні прогресу, стадіальних (позитивістських, марксистських) теоріях історії. Констатовано, що у зазначених теоріях розвиток (“прогрес”, історія) трактують як лінійне, поступове розгортання досягнень людства. Натомість циклічний, нелінійний розвиток людства з ідейних мотивів визначається як неможливий. Зміна кількісного глобального розвитку якісним забезпечується через біфуркацію. The notion of global development is considered. Olena Koppel argues that nature of the category “global development” is still unclear and precisely undefined in different scientific concepts. Nevertheless, scientists have considered its determinants, aspects, vectors, despite lack of precise explanation of this term in the wide and narrow sense. Considered concept has originated from a wider concept of development. The idea of development came out from linear historical views of eschatological religions (Judaism, Christianity, Islam, etc.), the Whig interpretation of progress, rationalistic and stages theory concepts of history proposed by positivists and Marxists and also from the meliorism principle. It is stated that these concepts consider concepts of progress and history as strictly linear, gradual, cumulative deployment of man and mankind achievements in all directions. From the perspective of these theories cyclic non-linear development is impossible because of its negative psychological and social consequences, in particular, due to the absence of progress as stressed by I. Wallerstein. And vice versa, the idea of progress is incompatible with concepts of relativism and degradation. The global (social) development, as a type of development in general, which includes international, national and human development is emphasized. The global development appears possible due to maintaining stability of global society. This stability is based on the mechanism of social inertia that provides heredity in global society and is embodied in structure of humanity differentiation for successful adaptation to natural environmental challenges. Global development includes two dialectically united dimensions. The first one is quantitative development as the changes in material culture, economy and humanity productivity. This kind of progress is based on usage of limited external (natural) resources. The second dimension is the qualitative development, i.e.changes in humanity nature, its culture. This development is based on usage of unlimited internal (cultural and psychological) resources of humanity. Connection between these measurements of global development is provided by bifurcation (overwhelming) during which the excess “degree” of certain quantitative indicators of global development causes changes in its quality.
The linear concept of global development: history and nature
Keywords: поняття; термін; політична теорія; глобалістика; глобальний розвиток; notion; category; political theory; global studies; global development